AGRICULTURAL STATISTICS: USING MULTIPLE MODES OF FOOD CROPS DATA COLLECTION IN INDONESIA DURING THE COVID-19 PANDEMIC - Amalia, Ratna Rizki (Universitas Islam Negeri Alauddin Makassar, 2020)
Government policy to limit the spread of COVID-19, such as lockdowns and social distancing, poses critical challenges to food crops data collection. The spread of COVID-19 has led to new challenges in collecting food crops data, which were previously collected using a conventional method, namely through measurements and direct interviews with respondents. To address this challenge, BPS-Statistics Indonesia finds alternatives to surveying by implemented multiple data collection modes, namely direct observation and measurement, physically distanced face-to-face interviews, and phone interviews. One of the most challenging aspects of implementing this combined method is the implementation of field activities. This issue arises due to an insufficient database of agricultural households' phone numbers and a questionnaire format that is complex enough to be used in this new method. This paper provides a comprehensive look at the technicalities that are implemented regarding this breakthrough. This paper's discussion focuses on the business process of data collection and strategic ways to overcome the challenges faced in implementing the method.